Oral Manifestations of HIV Disease - Raheem, Ahmed Salim; Okropiridze, Tamar (Caucasus Journal of Health Sciences and Public Health, 2016)
The range of manifestations of HIV-infection is extremely broad and may overlap with many diseases of the oral mucosa of different origin. These diseases can be divided into 2 groups: infectious diseases of the oral mucosa and tumour diseases of the oral mucosa (the diseases of unspecified origin such as recurrent aphthae could be included in the third group, respectively). Infectious diseases of the oral mucosa can occur within the ARC (the AIDS-related complex) and are common in patients with manifested AIDS. However, none of these manifestations is among the clinical criteria for the determination of HIV infection. The disease of the oral mucosa can manifest itself several months earlier than other HIV manifestations. Respective changes in the oral cavity can be the first clinical symptoms of the disease, none of them being specific only for HIV infection! This poses a problem from both the diagnostic and epidemiological point of view. Diseases with different etiologies may occur in one patient at the same time (mostly at a level of CD4+ Tlymphocytes below 200/mm3); patients with elevated levels of CD4+ T-lymphocytes (but still below 400/mm3) usually show only one kind of intraoral affliction in the oral cavity. Generally, infectious diseases of the oral mucosa can be divided into viral infections, bacterial infections and fungal infections. Since the clinical symptoms of the disease may appear long after the contact with the HIV virus (even laboratory tests may not give a reliable result for a certain period of time - 3-6 months), the medical staff should observe basic hygienic precautions and use protective gloves and a mouthpiece, when treating HIV patients. Most HIV-positive patients and patients with AIDS symptoms are treated in specialized clinics for infectious diseases. The patient is scheduled to have a dental treatment at the end of working hours. a) Tools for single use should be used as much as possible. b) The assisting nurse must decontaminate and wash the used tools after use, avoiding the formation of aerosol. Dry tools are sterilized in an autoclave or hot-air sterilizer. c) The attending physician and other medical staff should use a mouthpiece, cap, safety glasses, full-face shield, disposable clothing and two pairs of gloves (surgical and non-sterile protective!). d) The use of a turbine should be limited (aerosol) during preparation. e) After prosthetic treatment, all materials which were placed in the patient’s mouth are transported in a closed container to the laboratory and disinfected and sterilized prior to further processing (the laboratory technician should be protected in the same manner as the medical staff), f)X-ray images must be sealed in a plastic foil and submerged into an alcohol solution for disinfection, prior to development, g) All materials intended for disposal must be labelled as infectious (including clothing unless it is intended for single use only).